A Simple Yet Reliable Facial Emotion Detection For Campus Environment - Amar Lokman; Mus’ab Sahrim; Wan Zakiah Wan Ismail; Sharma Rao Balakrishnan; Juliza Jamaludin (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Volume:8 Issue:3